A technology of digitization of practical materials maps based on software programs Maplnfo Professional and CorelDRAW - A. I. Yakimchyk (Геофизический журнал, 2010)
A process of information input in the computer with the use of GIS MapInfo Professional and graphic software package CorelDRAW 11 is described in detail. It is shown, that working technique on the raster overlay allows to combine raster and vector layers, considerably increasing a digitizing accuracy and speed. The digitizing method does not require special devices as digitizer. It is offered to use for digitizing the inflicted on a map observations points and the anomaly values, but not isolines. The use of the right rectangular system of coordinates and the point coordinates fixing is substantial. The testing is executed on actual material and efficiency of the developed method of input of cartographic information in a computer is proved.